Acute myelopathy in association with heroin addiction. Issue 5 (May 1981) - Ell, J J; Uttley, D; Silver, J R
Abstract : The occurrence of spinal cord lesions in association with self-administration of heroin is a recognised entity in the United States of America which has not up to now been reported in British literature. Three cases are described, the literature reviewed and possible aetiological factors discussed.